An automatic system for Turkish word recognition using discrete wavelet neural network based on adaptive entropy - Avci, Engin (Springer Heidelberg, 2007)
In this paper, an automatic system is presented for word recognition using real Turkish word signals. This paper especially deals with combination of the feature extraction and classification from real Turkish word signals. A Discrete Wavelet Neural Network (DWNN) model is used, which consists of two layers: discrete wavelet layer and multi-layer perceptron. The discrete wavelet layer is used for adaptive feature extraction in the time-frequency domain and is composed of Discrete Wavelet Transform (DWT) and wavelet entropy. The multi-layer perceptron used for classification is a feed-forward neural network. The performance of the used system is evaluated by using noisy Turkish word signals. Test results showing the effectiveness of the proposed automatic system are presented in this paper. The rate of correct recognition is about % 92.58 for the sample speech signals.
Keywords: word recognition; Turkish word signal; feature extraction; DWT; entropy; wavelet neural networks; automatic system